“It felt like falling off a cliff”: the transition from prison to the community of people convicted of sexual offences - Saunders, Lynn (2020)
The number of people in prison in England and Wales with a current or previous conviction for a sexual offence has risen significantly in recent years, in part because of a growth in the number of convictions for historical offences over this period, but also as a result of growing recognition and understanding of the harm that sexual offending causes. Changes in legislation and developments in professional practice have taken place as a response to these legitimate concerns. This thesis critically analyses the expectations and experiences of people convicted of sexual offences in the transition from prison to the community. It also examines data from those responsible for their supervision. It explores and advances the established literature on desistance, risk assessment and risk management. The study data are analysed thematically. The six key findings cover: the impact of imprisonment on a person but also the benefits of the prison as a community; the importance and role of family support in reducing isolation; the positive impact of employment or purposeful activity on well-being; the importance of not simply the provision of accommodation but the opportunity to establish a home; the stigma and challenges of life in the community; and the importance of hope and planning for the future. It provides an insight from the perspective of the people involved in this challenging period. As a result, recommendations for improvements in policy and practice are made both to reduce reoffending and to improve the well-being of the individuals concerned.